In Defense of Workplace Democracy: Towards a Justification of the Firm–State Analogy. (February 2016) - Landemore, Hélène; Ferreras, Isabelle
In the wake of the 2008 global financial crisis, an important conceptual battleground for democratic theorists ought to be, it would seem, the capitalist firm. We are now painfully aware that the typical model of government in so-called investor-owned companies remains profoundly oligarchic, hierarchical, and unequal. Renewing with the literature of the 1970s and 1980s on workplace democracy, a few political theorists have started to advocate democratic reforms of the workplace by relying on an analogy between firm and state. To the extent that a firm is an organization comparable to the state, it too ought to be ruled along democratic lines. Our paper tests the robustness of the analogy between firm and state by considering six major objections to it: (1) the objection from a difference in ends, (2) the objection from shareholders' property rights, (3) the objection from worker's consent, (4) the objection from workers' exit opportunities, (5) the objection from workers' (lack of) expertise, and (6) the objection from the fragility of firms. We find all of these objections wanting. While the paper does not ambition to settle the issue of workplace democracy at once, our goal is to pave the way for a more in-depth study of the ways in which firms and states can be compared and the possible implications this may have for our understanding of the nature of managerial authority and the governance of firms.